2012
DOI: 10.1590/s0101-20612012005000015
|View full text |Cite
|
Sign up to set email alerts
|

Analytical characteristics and discrimination of Brazilian commercial grape juice, nectar, and beverage

Abstract: The production and commercialization of Brazilian grape juice is increasing annually, mainly due to its typicality, quality, and nutritional value. The present research was carried out in view of the great significance of Brazilian grape juice for the grape and wine industry. The purpose of this study, therefore, was to assess its composition as well as the discrimination between grape juice and other beverages. Twenty four samples of whole, sweetened, and reprocessed grape juices, grape nectar, and grape beve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 9 publications
7
18
6
2
Order By: Relevance
“…Rizzon and Miele [19] found values of 0.03 g/100g of acetic acid for whole juices, 0.05 g/100g of acetic acid for sweetened juices and 0.02 g/100g of acetic acid for the reprocessed juice, which are lower values than most found in this study. Gabardo et al [24] observed volatile acidity of 0.04 g/100g of acetic acid for both conventionally produced and organic white grape juice, those being low numbers when compared to the present work.…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…Rizzon and Miele [19] found values of 0.03 g/100g of acetic acid for whole juices, 0.05 g/100g of acetic acid for sweetened juices and 0.02 g/100g of acetic acid for the reprocessed juice, which are lower values than most found in this study. Gabardo et al [24] observed volatile acidity of 0.04 g/100g of acetic acid for both conventionally produced and organic white grape juice, those being low numbers when compared to the present work.…”
Section: Resultscontrasting
confidence: 84%
“…Rizzon and Link (2006) [18] analyzed homemade purple grape juices from different varieties and obtained density results on average of 1.055 which are lower than this study's results. Rizzon and Miele (2012) [19] evaluated commercial juices of three types (whole, sweetened and reprocessed), for which average density values were respectively, 1.069, 1.070 and 1.061, showing numbers very compatible with the present work. The lowest average value of alcohol content in purple grape juices was 0.27% (v/v) in the harvests of 2012 and 2015 while the highest mean was 0.43% in 2013.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…However, similar values were reported for magnesium (0.10 mg/100 g), sodium (0.042 mg/100g), and zinc (1.1 mg/100g). Rizzon & Miele (2012), investigating minerals in grape juice, found higher values of sodium (0.067 mg/100 g), potassium (129.5 mg/100g), phosphorus (10.5 mg/100g), and magnesium (8.78 mg/100g), but lower values of iron (0.14 mg/100g).…”
Section: Physicochemical Characterizationmentioning
confidence: 98%
“…Recently, society has shown a remarkable interest in the commercialization of juices and nectars in various forms (Carvalho et al, 2005). There is an incentive to produce grape juice because it has important nutritional properties (Burin et al, 2010) such as antioxidant activity due to the presence of phenolic compounds (Rizzon & Mielle, 2012).…”
Section: Introductionmentioning
confidence: 99%